Comparison of Accounting Profit Between Offshore and Deep-sea Commercial Fishing Industry in Pahang State, East Coast of Peninsular Malaysia - Moe Shwe Sin; Lavaniya Gopabala Krishnan; Shzee Yew Tai; Azlina Abd Aziz; Mahirah Kamaludin (Jurnal Ilmiah Perikanan dan Kelautan)
Highlight Research